A new species of Limnonectes (Amphibia: Anura: Dicroglossidae) from Vietnam - Pham, Cuong The; Do, Dang Trong; Le, Minh Duc; Ngo, Hanh Thi; Nguyen, Luan Thanh; Ziegler, Thomas; Nguyen, Truong Quang (Zootaxa, 2020)
A new species of Limnonectes from Phu Yen Province, South-central Vietnam is described based on morphological and molecular differences. Morphologically, the new species is distinguishable from its congeners on the basis of a combination of the following diagnostic characters: SVL 49.8–77.9 mm in males, 40.8–61.8 mm in females; males with moderately enlarged head (HL/SVL 0.47, HW/SVL 0.48); head slightly broader than long (HL/HW 0.97 in males, 0.95 in females); vomerine teeth present; external vocal sacs absent; rostral length short (RL/SVL 0.15); tympanum invisible; dorsal surface of head, body and flanks with ridges and tubercles; dorsal surface of tibia and foot distinctly tuberculate, covered with moderately dense, small, low tubercles; supratympanic fold present; dorsolateral fold absent; Finger I with nuptial pad, composed of minute spines on dorsal surface and medial edge in males; toes webbed to distal of terminal phalanx, webbing formula I0–0II0–0III0–0IV0-–0V0; in life, dorsum yellowish brown with dark brown markings; ventral surface white with brown markings. In phylogenetic analyses, the new species from Vietnam and Limnonectes fastigatus as well as L. kiziriani form a clade, which is sister to L. fragilis from China, although the nodal support values for the set of relationships are insignificant from all analyses.